An Analysis of Factors that Affecting the Number of Car Sales in Malaysia - Islam, Rabiul; Ghani, Ahmad Bashawir Abdul; Kusuma, Bobby; Ho, Eric Teh Yew (International Review of Management and Marketing, 2016)
This study investigates the relationship between macroeconomic variables and number of car sales in Malaysia. The main objective is to determine the factors that affecting the number of car sales in Malaysia. This research covers the time period from 1985 to 2014. The analysis methods that have been applied in this study include descriptive statistics, multiple regression statistics and correlation analysis. The findings shows that GDP has positive relationship with the number of car sales in Malaysia, while interest rate, unemployment rate and inflation rate have negative relationship with the number of car sales in Malaysia. The findings were consistent with the previous findings done by other researcher. Keywords: Car sale, GDP, interest rate, unemployment rate, inflation rate JEL Classifications: J6, L81